Integration of computation methods in dosimetry of radiation processing - Lazurik, V.T.; Lazurik, V.M.; Popov, G.F.; Rogov, Y.V. (Вопросы атомной науки и техники, 2008)
Software for modelling by Monte Carlo (MC) method the dosimetric devices such as dosimetric wedge (ModeDW) and stack (ModeStEB) irradiated with scanned electron beam on moving conveyer was developed by authors. Integration of computer modelling of a dose distribution in films located in a wedge and stack made of arbitrary materials expands the procedure opportunities of the dosimetric devices in the dosimetry of radiation processing. Розроблено програмне забезпечення для моделювання методом Монте-Карло дозиметричних приладів, таких як дозиметричний клин (ModeDW) та пакет (ModeStEB), які опромінюються сканованим пучком електронів на конвеєрі, що рухається. Інтегрування комп'ютерного моделювання розподілу дози в плівках, які розташовані в клині та пакеті з довільного матеріалу розширюють методичні можливості цих дозиметричних приладів в дозиметрії радіаційних технологій. Разработано программное обеспечения для моделирования методом Монте-Карло дозиметрических устройств, таких как дозиметрический клин (ModeDW) и пакет (ModeStEB), облучаемых сканирующим пучком электронов на движущемся конвейере. Интегрирование компьютерного моделирования распределения дозы в пленках, расположенных в клине и пакете, изготовленных из произвольных материалов, расширяет методические возможности этих дозиметрических устройств в дозиметрии радиационных технологий.